Preparation method of surface-modified high-purity nano zirconium dioxide powder
Through mechanical stirring and grinding and modification methods, the surface of high -purity nano dioxide pink pinks is relocated, solving the problem of equipment blockage and reunion caused by the hydrophilicity of the powder, and realized the characteristics of water hate and better mixing uniformly. Sexuality improves the performance of lithium batteries.
Patent Information
- Application Number
- CN202411396552.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
AI Technical Summary
When high-purity nanozirconium dioxide powder is used in the positive electrode material of ternary lithium battery, it has high moisture content due to its hydrophilicity, which causes clogging, agglomeration and uneven mixing of airflow crushing equipment, affecting the performance of the electrode material.
Through the mechanical stirring and grinding modification method, oily organic matter is used as a surface modifier, and the modifier is grafted on the surface of the powder particles through the stirring action of the sand mill to form a hydrophobic surface, thereby reducing the water content.
The water hate characteristics of high -purity nano dioxide powder are realized, the problem of equipment blockage and gathering is avoided, the sieve rate and mixed uniformity of the powder are improved, and the performance of the lithium battery is enhanced.
Smart Images

Figure CN119349630A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of new zirconium oxide materials, and in particular relates to a method for preparing surface-modified high-purity nano zirconium dioxide powder. Background Art
[0002] A large number of studies have shown that doping a small amount of high-purity nano zirconium dioxide in the positive electrode material of ternary lithium batteries will improve the material structure stability of ternary lithium batteries, reduce the impedance during the charge and discharge process, and increase the charge and discharge cycle life. The simplest way to mass-produce doped nano high-purity nano zirconium dioxide powder is to evenly mix the ternary positive electrode material and high-purity nano zirconium dioxide powder in a high-speed mixer, then sinter at about (700-800)℃, and then crush and screen to obtain the ternary positive electrode material modified with high-purity nano zirconium dioxide powder.
[0003] There are many production and preparation methods for high-purity nano zirconium dioxide powder on the market, mainly hydrothermal method, hydrolysis method and co-precipitation method. Although high-purity nano zirconium dioxide powder is insoluble in water, its wetting angle with water is 0 degrees, and it is easily wetted by water. At the same time, the high-purity nano zirconium dioxide powder used in ternary positive electrode materials has a large specific surface area, usually 30-50m 2 / g, resulting in an increase in the amount of water adsorbed on the surface of high-purity nano zirconium dioxide powder. The mass fraction of water in high-purity nano zirconium dioxide powder produced under normal conditions can reach 1.0%-1.5%. In order to mix evenly with the ternary positive electrode material, the high-purity nano zirconium dioxide powder is granulated and then air-flow crushed to achieve low looseness and good dispersibility. The high water content of the powder will cause the air flow pipeline to be blocked after the air flow crushing equipment has been running for a period of time, and a hard agglomerate layer of powder will be formed on the tube wall. After these powder lumps fall off, it will affect the fineness and uniformity of the final powder. In addition, there are multiple links in the subsequent process that come into contact with water, which leads to several agglomerations and difficulties in uniform mixing. The powder sieved after the air flow will still agglomerate and become agglomerates due to the hydrophilic properties of the high-purity nano zirconium dioxide powder during the subsequent storage process due to the self-adhesiveness of the nano powder with high water content. Even if the water is removed by drying before production, if it is exposed to air during the production process, it will still quickly absorb water and cause agglomeration. When it is mixed with the ternary positive electrode material through a high-speed mixer, it cannot be dispersed and mixed evenly, resulting in local high-purity nano zirconium dioxide powder agglomeration lumps. These agglomerated lumps are not only easy to adhere to the stainless steel screen, seriously blocking the screen and affecting production, but more seriously, it leads to uneven composition of the ternary material after doping, and the performance of the electrode material is greatly reduced.
[0004] In order to solve this problem, it is a feasible approach to modify the surface of high-purity nano zirconium dioxide powder to obtain a hydrophobic surface and significantly reduce the water content of high-purity nano zirconium dioxide powder.
[0005] In the prior art, CN115893486A "Method for Modifying Zirconium Oxide Powder and Modified Zirconium Oxide Powder" uses water glass to activate the zirconium oxide powder, and then adds silane modifiers to obtain completely hydrophobic zirconium oxide powder materials. Although this patent achieves the modification of powder from hydrophilic to hydrophobic, both water glass and silane modifiers contain a large amount of sodium and silicon elements, which will cause the purity of zirconium oxide powder to decrease and cannot be used in the doping of lithium battery ternary positive electrode materials. Yang Xiaomin's "Study on Surface Modification and Performance of Nano 3Y-TZP Ceramic Powder" uses 10% lauric acid to modify the powder at 60°C for 75 minutes. Excessive use of modifiers not only increases production costs but also causes serious environmental pollution during the later sintering process. At the same time, the modification time is long and there is a temperature limit, resulting in excessive use of modifiers, which is not conducive to mass production. Hou Chao's "Study on Surface Modification of Zirconia and Its Gel Injection Molding Process" used 0.4% chelated titanate coupling agent and 0.6%-0.8% silane coupling agent to modify the powder model. These modifiers introduced impurities of titanium and silicon, which is not conducive to obtaining high-purity electronic-grade nano zirconium dioxide powder. Liang Yue's "Surface Modification of Zirconia Powder" used 0.8% PVP (K90) and 3% PEG200 to modify the powder to obtain softer powder particles with better spherical shape and easy molding. The PVP and PEG200 used in this method have good water solubility and cannot play a good hydrophobic role in the modification of high-purity nano zirconium dioxide powder. Summary of the invention
[0006] In order to overcome the deficiencies in the prior art, the present invention provides a method for preparing surface-modified high-purity nano zirconium dioxide powder. The method aims to provide a method for simply and quickly mechanically stirring and grinding the high-purity nano zirconium dioxide powder without introducing metal element impurities such as silicon and titanium, so that the high-purity nano zirconium dioxide powder has hydrophobic properties, thereby solving the related problems generated in the process of doping the ternary positive electrode material with high-purity nano zirconium dioxide mixing during its own production process.
[0007] The present invention provides the following technical solution: a method for preparing surface-modified high-purity nano zirconium dioxide powder, which comprises the following steps:
[0008] 1) Take high-purity nano zirconium dioxide calcined powder, mix the ingredients according to the ratio of calcined powder mass to pure water = 1.0: 1.0-1.5, add the mixture to a drum ball mill and grind it to D50 < 0.5 μm, transfer the slurry to a sand mill, add a dispersant and continue grinding it to D50 < 0.15 μm to obtain high-purity nano zirconium dioxide slurry A;
[0009] 2) 1-2%wt of oily organic matter is taken as a surface modifier, and the mixture is uniformly mixed in a ratio of oily matter to alcoholic matter = 1:6-8 to obtain solution B;
[0010] 3) Slowly add solution B into slurry A to form slurry C, and continue to grind and mix slurry C in a sand mill for 1 to 2 hours, so that the modifier oily organic matter in solution B is grafted onto the surface of the powder particles through the action of the stirring mechanical force;
[0011] 4) The sand-milled slurry C is spray granulated to obtain spherical powder D, and the grafting is irreversible during high-temperature drying, so that the powder surface is truly grafted with the modifier. The spherical powder D is crushed by air flow crushing equipment to obtain low-loose surface-modified high-purity nano zirconium dioxide powder E.
[0012] Preferably, the high-purity nano zirconium dioxide calcined powder in step 1) has a Cl- content of less than 200 ppm, a Na+ content of less than 200 ppm, and a specific surface area of 0-100 m 2 / g.
[0013] Preferably, the high-purity nano zirconium dioxide calcined powder in step 1) is Cl - Less than 200ppm, Na + Less than 200ppm, specific gravity is 25-100m 2 / g.
[0014] Preferably, the dispersant in step 1) is a dispersant with a neutral pH value, including DolaPIX CE 64 , ammonium polyacrylate.
[0015] Preferably, the modified organic matter in step 2) includes one or more of linoleic acid, triglyceride acetate, methyl palmitoleate and stearyl alcohol.
[0016] Preferably, the alcohol substance in step 2) includes one or more of propanol, isopropanol, ethylene glycol, and methanol.
[0017] Preferably, the stirring speed of the sand mill in step 3) should be 500-1000 rpm.
[0018] Preferably, in step 4), the inlet drying temperature of the granulation tower is between 260-280°C, and the outlet temperature is between 95-105°C.
[0019] Beneficial effects of the present invention:
[0020] The invention discloses a preparation method of surface-modified high-purity nano zirconium dioxide powder. The high-purity nano zirconium dioxide slurry is first ground to a nanometer level, and then an oily modifier is melted in an alcohol compound and then added to the high-purity nano zirconium dioxide slurry. The modifier is first evenly dispersed in the slurry through the mechanical stirring and grinding action of a sand mill, and the surface of the high-purity nano zirconium dioxide powder absorbs -COOH and -OH on specific alcohol compounds and specific oily compounds due to its hydrophilicity. More active hydroxyl groups on the surface of the high-purity nano monoclinic zirconium dioxide powder particles are chemically bonded to the carboxyl groups of the modifier and thus grafted onto the particles. The two are bonded through covalent bonds rather than simple surface adsorption. Then, the excess water is removed through spray granulation and drying, so that the adsorption is irreversible. Since the modifier will form a slightly viscous emulsion when added to the material, if the speed is too low, it will not be fully and evenly grafted. If the speed is too high, the machine will not be able to operate due to excessive liquid resistance. If the temperature of the granulation tower is too low, the oily modifier will not be firmly grafted on the surface of the powder particles. If the temperature is too high, the modifier molecules will decompose and become ineffective. The modifier molecules are firmly grafted on the surface of the high-purity nano zirconium dioxide powder particles, so that the high-purity nano zirconium dioxide powder changes from hydrophilic to hydrophobic. The obtained powder will not block the equipment during airflow processing, and will not form thick powder agglomerates on the equipment pipe wall (this agglomerate is also easy to mix into the final powder product). Moreover, the modified powder is easy to store and does not require multi-layer storage with desiccant. It does not have excessive requirements for the moisture in the use environment. It is more uniform when mixed in the ternary positive electrode material, and is easy to screen, which improves the performance of the final lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Table 1 Comparison of powder parameters of the embodiment and the comparative example;
[0022] Figure 1 The hydrophobicity test results of the powder of Example 1;
[0023] Figure 2 The hydrophobicity test results of the powder of Example 1;
[0024] Figure 3 Figure 2 The result was obtained after ultrasonic stirring in a beaker for 5 minutes;
[0025] Figure 4 Comparative Example 1: Hydrophobicity test results of powder;
[0026] Figure 5 The water increase test results of the powder of Comparative Example 1;
[0027] Figure 1 and Figure 4The test rules for hydrophobicity are as follows: take the final modified air flow powder and press it flat in a square groove. Use a dropper to drop a drop of pure water on the flattened surface and wait for 1 minute to observe the contact between the droplet and the flattened surface of the powder.
[0028] Figure 2 , Figure 3 and Figure 5 According to the hydrophobicity test rules, take 1g of the final air flow crushing powder, put it into a beaker filled with 200ml of pure water, stir it with a glass rod for 1min, and then let it stand for 1min, and observe the state of the powder in the water. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further explained below by examples, but the protection scope of the present invention is not limited in any form by the examples.
[0030] The moisture content in Table 1 of this application is measured at 120°C using an infrared online moisture meter; the bulk density is measured in accordance with GB / T31057.1; the water absorption rate is measured by taking 50g of the prepared powder and drying it in an oven at 100°C for 2h, taking it out and putting it in a dryer to cool it to room temperature, weighing the mass and then placing it in an atmospheric environment at room temperature for 1h, and weighing the mass again to see the percentage of mass increase; the sieving rate is measured by taking 50g of the prepared modified powder and shaking it with a 0.2mm stainless steel sieve for 5min, and then weighing the mass of the sieve and the sieve respectively, and observing the agglomeration state of the sieve. Water contact angle test: Take the final modified airflow powder and flatten it in a square groove, take 5μL of deionized water and drop it on the flattened powder surface respectively, use the JC2000D4M contact angle tester to test the surface contact angle, and measure 10 times at different positions on the same sample to take the average value.
[0031] Embodiment 1:
[0032] Specific surface area 50m 2 / g coprecipitation method high-purity nano zirconium dioxide calcined powder, by taking 0.4g of calcined powder ground through a 0.1mm sieve, adding 40ml acetic acid and ultrasonic for 10min, the dissolution test Cl - The content of Na in the dissolved powder was 146 ppm. 0.4 g of calcined powder ground through a 0.1 mm sieve was added to 200 ml of deionized water and ultrasonicated for 2 h. + It is 48ppm.
[0033] 180 kg of the calcined powder was taken and added to a ball mill according to the ratio of calcined powder: pure water = 1:1.4, and ball milled for 10 hours. The average particle size of the slurry was 0.45 μm. The slurry was then transferred to a sand mill and 0.2% of DolaPIXCE64 dispersant was added and continued to grind for 6 hours. The average particle size of the slurry was 0.13 μm. The slurry solution at this time was A. 0.5% of linoleic acid (0.9 kg) and 0.5% of triacetin (0.9 kg) relative to the calcined powder and 6 times the total weight of isopropanol (10.8 kg) of linoleic acid and triacetin were mixed and stirred to obtain solution B. Solution B was slowly added into the sand mill where solution A was located, and grinding was continued at 800 rpm for 1 hour to modify the powder to obtain emulsion C. The emulsion C was transferred to a granulation tower and dried and granulated at an inlet temperature of 260°C and an outlet temperature of 100°C to obtain powder D. Powder D was crushed in an air flow crushing device using 8 kg of dry pure air to obtain low-loose surface-modified high-purity nano zirconium dioxide powder E.
[0034] Take a small amount of powder E to test moisture, bulk density, water absorption, sieving performance and hydrophobicity, among which:
[0035] The moisture content is measured at 120°C using an infrared moisture meter. The bulk density is measured in accordance with GB / T 31057.1. For water absorption, 50g of the prepared powder is first dried in an oven at 100°C for 2h, taken out and placed in a dryer to cool to room temperature, weighed and placed in an atmospheric environment at room temperature for 1h, and weighed again to see the water absorption. For the sieving of the powder, 50g of the prepared modified powder is shaken and sieved with a 0.2mm stainless steel sieve for 5min, and the masses of the sieve and the sieve are weighed respectively, and the agglomeration state of the sieve is observed. For the hydrophobicity of the powder, 5g of the powder is added to pure water and stirred for 1min to observe the state of the powder in the water, and then ultrasonically observed for 5min.
[0036] Embodiment 2:
[0037] Take the specific surface area of 50m 2 / g coprecipitation method of high-purity nano zirconium dioxide calcined powder, by taking 0.4g of calcined powder ground through a 0.1mm sieve, adding 40ml acetic acid and ultrasonically dissolving for 10min to test Cl - The content of Na in the powder was 146 ppm. 0.4 g of calcined powder was ground through a 0.1 mm sieve and added to 200 ml of deionized water and ultrasonically dissolved for 2 h. + It is 48ppm.
[0038] Take 180 kg of the calcined powder, add it to a ball mill according to the ratio of calcined powder: pure water = 1:1.4, and ball mill for 10 hours. The average particle size of the slurry is 0.45 μm. Then transfer the slurry to a sand mill and add 0.2% polyacrylic acid and continue grinding for 6 hours. The average particle size of the slurry is 0.13 μm. The slurry solution at this time is A. Mix 1% of linoleic acid (1.8 kg) relative to the mass of the calcined powder and 6 times the weight of ethylene glycol (10.8 kg) of linoleic acid and stir evenly to obtain solution B. Slowly add solution B to the sand mill where solution A is located and continue grinding at 1000 rpm for 1.5 hours to modify the powder to obtain emulsion C. Transfer emulsion C to a granulation tower with an inlet temperature of 280°C and an outlet temperature of 105°C for drying and granulation to obtain powder D. Powder D is crushed in an air flow crushing device. 8 kg of dry pure air is used for crushing to obtain low-loose surface-modified high-purity nano zirconium dioxide powder E.
[0039] Take a small amount of powder E to test moisture, bulk density, water absorption, sieving performance and hydrophobicity, among which:
[0040] The moisture content is measured at 120°C using an infrared moisture meter. The bulk density is measured in accordance with GB / T 31057.1. For water absorption, 50g of the prepared powder is first dried in an oven at 100°C for 2h, taken out and placed in a dryer to cool to room temperature, weighed and placed in an atmospheric environment at room temperature for 1h, and weighed again to see the water absorption. For the sieving of the powder, 50g of the prepared modified powder is shaken and sieved with a 0.2mm stainless steel sieve for 5min, and the masses of the sieve and the sieve are weighed respectively, and the agglomeration state of the sieve is observed. For the hydrophobicity of the powder, 5g of the powder is added to pure water and stirred for 1min to observe the state of the powder in the water, and then ultrasonically observed for 5min.
[0041] Embodiment 3:
[0042] Take the specific surface area of 50m 2 / g coprecipitation method of high-purity nano zirconium dioxide calcined powder, by taking 0.4g of calcined powder ground through a 0.1mm sieve, adding 40ml acetic acid and ultrasonically dissolving for 10min to test Cl - The content of Na in the powder was 146 ppm. 0.4 g of calcined powder was ground through a 0.1 mm sieve and added to 200 ml of deionized water and ultrasonically dissolved for 2 h. + It is 48ppm.
[0043] 180 kg of the calcined powder was taken and added to a ball mill according to the ratio of calcined powder: pure water = 1:1.4, and ball milled for 10 hours. The average particle size of the slurry was 0.45 μm. The slurry was then transferred to a sand mill and 0.1% DolaPIXCE64 and 0.1% ammonium polyacrylate were added and continued to grind for 8 hours. The average particle size of the slurry was 0.16 μm. The slurry solution at this time was A. 1% of palmitoleic acid methyl ester (1.8 kg) relative to the mass of the calcined powder and 6 times the weight of palmitoleic acid methyl ester (10.8 kg) were mixed and stirred to obtain solution B. Solution B was slowly added into the sand mill where solution A was located, and the powder was continuously ground at 100 rpm for 1 h to obtain modified powder, and emulsion C was obtained. The emulsion C was transferred to a granulation tower, and dried and granulated at an inlet temperature of 270°C and an outlet temperature of 105°C to obtain powder D. Powder D was crushed in an air flow crushing device, and 8 kg of dry pure air was used for crushing, to obtain low-loose surface-modified high-purity nano zirconium dioxide powder E.
[0044] Take a small amount of powder E to test moisture, bulk density, water absorption, sieving performance and hydrophobicity, among which:
[0045] The moisture content is measured at 120°C using an infrared moisture meter. The bulk density is measured in accordance with GB / T 31057.1. For water absorption, 50g of the prepared powder is first dried in an oven at 100°C for 2h, taken out and placed in a dryer to cool to room temperature, weighed and placed in an atmospheric environment at room temperature for 1h, and weighed again to see the water absorption. For the sieving of the powder, 50g of the prepared modified powder is shaken and sieved with a 0.2mm stainless steel sieve for 5min, and the masses of the sieve and the sieve are weighed respectively, and the agglomeration state of the sieve is observed. For the hydrophobicity of the powder, 5g of the powder is added to pure water and stirred for 1min to observe the state of the powder in the water, and then ultrasonically observed for 5min.
[0046] Comparative Example 1: Specific surface area 52m 2 / g of coprecipitation high-purity nano zirconium dioxide calcined powder, tested by acetic acid dissolution Cl - The Na content in the powder is 160 ppm, which is measured by ultrasonic dissolution in water. + It is 45ppm.
[0047] Take 180 kg of the above calcined powder and add it into a ball mill at a ratio of calcined powder: pure water = 1:1.4, and ball mill for 10 hours. The average particle size of the slurry is 0.45 μm. Then transfer the slurry to a sand mill, add 0.2% DolaPIXCE64 dispersant and continue grinding at 800 revolutions for 6 hours. The average particle size of the slurry is 0.13 μm. The slurry solution at this time is A1. Solution A1 is spray granulated at an inlet temperature of 270°C and an outlet temperature of 100°C to obtain spherical granulated powder B1. Powder B1 is crushed in an air flow crushing equipment to obtain low-loose surface-modified high-purity nano zirconium dioxide nanopowder C1.
[0048] Take a small amount of powder C1 to test moisture, bulk density, water absorption, sieving performance and hydrophobicity, among which:
[0049] The moisture content was measured at 120°C using an infrared moisture meter, and the bulk density was measured in accordance with GB / T 31057.1. For water absorption, 50g of the prepared powder was first dried in an oven at 120°C for 2h, taken out and placed in a dryer to cool to room temperature, weighed and placed in an atmospheric environment at room temperature for 1h, and weighed again to see the water absorption. For powder sieving, 50g of the prepared modified powder was shaken and sieved with a 0.2mm stainless steel sieve for 5min, and the masses of the sieve under and on were weighed respectively, and the agglomeration state before the sieve was observed. For the hydrophobicity of the powder, 5g of the powder was added to pure water and stirred for 1min to observe the state of the powder in the water, and then ultrasonicated for 5min to observe the state of the powder in the water.
[0050] Comparative Example 2: Take a specific surface area of 50m 2 / g coprecipitation method of high-purity nano zirconium dioxide calcined powder, by taking 0.4g of calcined powder ground through a 0.1mm sieve, adding 40ml acetic acid and ultrasonically dissolving for 10min to test Cl - The content of Na in the powder was 146 ppm. 0.4 g of calcined powder was ground through a 0.1 mm sieve and added to 200 ml of deionized water and ultrasonically dissolved for 2 h. + It is 48ppm.
[0051] 180 kg of the calcined powder was taken and added to a ball mill according to the ratio of calcined powder: pure water = 1:1.4, and the ball mill was performed for 10 hours. The average particle size of the slurry was 0.45 μm. The slurry was then transferred to a sand mill and 0.2% ammonium polyacrylate dispersant was added and continued to grind for 8 hours. The average particle size of the slurry was 0.16 μm. The slurry solution at this time was A. 1% of linoleic acid (1.8 kg) relative to the mass of the calcined powder was slowly added to the sand mill where the solution A was located and continued to grind at 800 rpm for 1 hour to modify the powder to obtain an emulsion C. The emulsion C was transferred to a granulation tower with an inlet temperature of 270°C and an outlet temperature of 105°C for drying and granulation to obtain powder D. Powder D was crushed in an air flow crushing device, and 8 kg of dry pure air was used for crushing to obtain low-loose surface-modified high-purity nano zirconium dioxide powder E.
[0052] Take a small amount of powder E to test moisture, bulk density, water absorption, sieving performance and hydrophobicity, among which:
[0053] The moisture content is measured at 120°C using an infrared moisture meter. The bulk density is measured in accordance with GB / T 31057.1. For water absorption, 50g of the prepared powder is first dried in an oven at 100°C for 2h, taken out and placed in a dryer to cool to room temperature, weighed and placed in an atmospheric environment at room temperature for 1h, and weighed again to see the water absorption. For the sieving of the powder, 50g of the prepared modified powder is shaken and sieved with a 0.2mm stainless steel sieve for 5min, and the masses of the sieve and the sieve are weighed respectively, and the agglomeration state of the sieve is observed. For the hydrophobicity of the powder, 5g of the powder is added to pure water and stirred for 1min to observe the state of the powder in the water, and then ultrasonically observed for 5min.
[0054] Table 1
[0055]
[0056] Note: Since the specific surface area after modification cannot be accurately measured, the specific surface area shall be based on the test result after drying the grinding slurry before modification.
[0057] From Examples 1, 2, 3 and Comparative Examples 1 and 2, it can be seen that after the modification of the high-purity nano zirconium dioxide powder, pure water forms spheres on its surface ( Figure 1 ), add the powder into pure water and stir it. The powder is not compatible with water and completely floats on the surface of the water ( Figure 2 ), even after strong ultrasound, only a small amount of powder in pure water makes the water turbid ( Figure 3 ), indicating that the modifier can be firmly grafted on the surface of the powder particles, which is easy to store, transport and use for a long time. However, for the unmodified high-purity nano zirconium dioxide powder obtained in the comparative example 1, pure water drops on the surface layer of the powder will be directly flattened and absorbed by the powder layer ( Figure 4), after adding the powder into pure water and stirring, the powder will be completely immersed in the pure water to form a turbid liquid state. From Table 1, it can be seen that in Comparative Example 2, since no solvent solution is used to dissolve linoleic acid and triacetin in advance and then added to the sand mill, the modifier and the slurry cannot be directly dissolved and contacted, and the modifier molecules cannot fully and evenly contact with the slurry particles to better adsorb the grafted modifier molecules. Therefore, the final nano air flow crushed powder has a certain water absorption and cannot be fully sieved.
[0058] The present invention provides a method for preparing surface-modified high-purity nano zirconium dioxide powder, which mainly comprises the following steps:
[0059] 1) Take high-purity nano zirconium dioxide calcined powder with a specific ratio, specific chloride ions and specific sodium ions, mix the ingredients according to the ratio of calcined powder mass to pure water = 1.0: 1.0-1.5, add the mixture to a drum ball mill and mill it to D50 < 0.5 μm, transfer the slurry to a sand mill, add a dispersant and continue sand milling to D50 < 0.15 μm to obtain a high-purity nano zirconium dioxide slurry solution A.
[0060] 2) Take 1-2%wt of oily organic matter as a surface modifier, and mix them evenly according to the ratio of oily matter: alcoholic matter = 1:6-8 to obtain solution B.
[0061] 3) Solution B is slowly added to solution A to form solution C. Solution C is continuously ground and mixed in a sand mill for 1 to 2 hours, so that the modifier oily organic matter in solution B is grafted onto the surface of the powder particles through the mechanical force of stirring.
[0062] 4) The sand-milled solution C is spray granulated to obtain spherical powder D, and the grafting is irreversible during high-temperature drying, so that the powder surface is truly grafted with the modifier. The spherical powder D is crushed by air flow crushing equipment to obtain low-loose surface-modified high-purity nano zirconium dioxide powder E.
[0063] In the above steps, the stirring speed of the sand mill should be 500-1000 rpm. Since the modifier will form a slightly viscous emulsion when added to the material, too low a speed will not allow for full and uniform grafting, and too high a speed will cause the machine to fail to operate due to excessive liquid resistance. The inlet drying temperature of the granulation tower is between 260-280°C, and the outlet temperature is between 95-105°C. Too low a temperature will cause the oily modifier to not be firmly grafted on the surface of the powder particles, and too high a temperature will cause the modifier molecules to decompose and fail.
[0064] The invention discloses a preparation method of surface-modified high-purity nano zirconium dioxide powder, which comprises the following steps: grinding high-purity nano zirconium dioxide calcined powder to a particle size of less than 0.15 microns by a ball mill and a sand mill, then adding a mixed solution of oily substances and alcohols, continuing sand milling to graft uniformly, granulating the uniformly sanded slurry liquid at high temperature to obtain modified granulated powder, crushing the modified granulated powder by an air flow crusher to obtain low-loose surface-modified high-purity nano zirconium dioxide powder, and sintering the surface of the modified high-purity nano zirconium dioxide powder by carboxylation. The base is evenly grafted with oleic acid, and the macromolecular groups on the surface of the powder allow the powder to completely float on the water surface, which is completely different from the high-purity nano zirconium dioxide powder before modification. The powder will not agglomerate in the sieve and basically will not block the sieve. The modified powder has stable moisture content and does not require dehumidification of the powder production environment, excessive packaging of the powder, or addition of desiccant to prevent the powder from absorbing water. It also prevents the powder from agglomerating during storage and the subsequent doping of ternary lithium battery positive electrode materials, which causes uneven mixing and large particles clogging the sieve.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing surface-modified high-purity nano zirconium dioxide powder, characterized in that: The following steps are included: 1) Take high-purity nano zirconium dioxide calcined powder, mix the ingredients according to the ratio of calcined powder mass to pure water = 1.0: 1.0-1.5, add the mixture to a drum ball mill and grind it to D50 < 0.5 μm, transfer the slurry to a sand mill, add a dispersant and continue grinding it to D50 < 0.15 μm to obtain high-purity nano zirconium dioxide slurry A; 2) 1-2%wt of oily organic matter is taken as a surface modifier, and the mixture is uniformly mixed in a ratio of oily organic matter to alcoholic substance = 1:6-8 to obtain solution B; 3) Slowly add solution B into slurry A to form slurry C, and continue to grind and mix slurry C in a sand mill for 1 to 2 hours, so that the modifier oily organic matter in solution B is grafted onto the surface of the powder particles through the action of the stirring mechanical force; 4) The sand-milled slurry C is spray granulated to obtain spherical powder D, and the grafting is irreversible during high-temperature drying, so that the powder surface is truly grafted with the modifier. The spherical powder D is crushed by air flow crushing equipment to obtain low-loose surface-modified high-purity nano zirconium dioxide powder E.
2. The method for preparing the surface-modified high-purity nano zirconium dioxide powder according to claim 1, characterized in that: The high-purity nano zirconium dioxide calcined powder in step 1), Cl - Less than 200ppm, Na + Less than 200ppm, specific gravity is 0-100m 2 / g.
3. The method for preparing the surface-modified high-purity nano zirconium dioxide powder according to claim 1, characterized in that: The high-purity nano zirconium dioxide calcined powder in step 1), Cl - Less than 200ppm, Na + Less than 200ppm, specific gravity is 25-100m 2 / g.
4. The method for preparing the surface-modified high-purity nano zirconium dioxide powder according to claim 1, characterized in that: The dispersant in step 1) is a dispersant having a neutral pH value, including DolaPIX CE 64 , one or more of ammonium polyacrylate.
5. The method for preparing the surface-modified high-purity nano zirconium dioxide powder according to claim 1, characterized in that: The oily organic matter in step 2) includes one or more of linoleic acid, triglyceride acetate, methyl palmitoleate and stearyl alcohol.
6. The method for preparing the surface-modified high-purity nano zirconium dioxide powder according to claim 1, characterized in that: The alcohol substance in step 2) includes one or more of propanol, isopropanol, ethylene glycol, and methanol.
7. The method for preparing the surface-modified high-purity nano zirconium dioxide powder according to claim 1, characterized in that: In step 3), the stirring speed of the sand mill should be 500-1000 rpm.
8. The method for preparing the surface-modified high-purity nano zirconium dioxide powder according to claim 1, characterized in that: In step 4), the inlet drying temperature of the granulation tower is between 260-280°C, and the outlet temperature is between 95-105°C.
Citation Information
Patent Citations
Method for modifying zirconia powder, and modified zirconia powder
CN115893486A